Hydrometallurgical recycling of waste NdFeB magnets: design of experiment, optimisation of low concentrations of sulphuric acid leaching and process analysis. (2nd January 2023) - Uysal, Emircan; Al, Serhat; Emil-Kaya, Elif; Stopic, Srecko; Gürmen, Sebahattin; Friedrich, Bernd
ABSTRACT: Efficient recovery of rare earth elements (REEs) from scrap NdFeB magnets is a significant requirement for a circular economy. Therefore, the development of a cost-effective and environmentally friendly leaching process for the dissolution of iron and REEs has received extensive interest. In this study, the dissolution of NdFeB magnet powders in sulphuric acid solution was investigated in detail. Taguchi orthogonal array was employed for the first time to define and optimise the influence of sulphuric acid concentration, solid-to-liquid ratio and stirring speed on the extraction of iron and rare earth elements (REEs). The acid concentration of sulphuric acid was determined as a key factor for iron and REEs dissolution, while solid-to-liquid ratio and stirring speed slightly affected the dissolution of REEs and iron. Maximum iron and REEs extraction were achieved under optimal conditions as the sulphuric acid concentration of 1 M, solid-to-liquid ratio of 1/15 and stirring speed of 350 rev min −1 . Consequently, after the validation experiment, it was proved that the design of experiments based on Taguchi orthogonal array is an efficient way for the optimisation of process parameters.